The Significance of Buddhist Philosophy for International Peacebuilding (International Journal of Environmental Sciences, 2024)
Finding effective peacebuilding backgrounds is more significant than ever in a world that is becoming more and more constant in terms of communication, violence, and societal conflict. Among other intellectual traditions, Buddhist philosophy stands out as a valuable source of guidance and wisdom for advancing global peace. Buddhism offers a unique perspective on social peace and conflict resolution that transcends cultural and theological differences since it is founded on the concepts of interconnectedness, compassion, and mindfulness. At its core, Buddhist philosophy emphasizes how important it is to understand the transience of things and the nature of suffering. This information encourages individuals and communities to foster empathy, reduce prejudice, and engage in meaningful dialogue.The Middle Path and non-attachment wisdoms inspire self-control, equilibrium, and an understanding of our common humankind—all of which are essential for passivequarrel settlement. Furthermore, by encouraging individuals to consider the broader implications of their decisions, the Buddhist concept of "Right Action" in the Eightfold Path promotes moral behaviour and social responsibility.This ethical framework can serve as a guide for world leaders and policymakers who want to encourage respect and cooperation among nations. The active participation of Buddhist scholars and leaders in global peace initiatives in recent years has demonstrated the importance of Buddhist philosophy to contemporary peacebuilding efforts.Buddhist ideas are used in programs that prioritize communication, community building, and peace-making to address the underlying causes of conflict and advance enduring peace. When considering Buddhist philosophy's applicability to international peacebuilding, it is imperative to consider both its theoretical foundations and practical applications. By applying these ideas to peacebuilding initiatives, we can discover ways to create a society that is less violent and were compassion and selflessness result in enduring peace. In addition to showing how useful Buddhism is in resolving global issues, this inquiry encourages a more thorough examination of the ways in which other philosophical traditions could support a peaceful future.